Stability Analysis Of The Bullying Model With The Factor Of Changing The Nature Of The Victim To Become A Bullies - Marshellino Marshellino; Abyan Daffa Akbar (Journal of Fundamental Mathematics and Applications (JFMA), 2026)
Bullying cases in Indonesia have increased over time. One of the places where the most bullying cases occur is in the educational environment, namely a form of abusive behaviour when students show aggressive behaviour that lasts a long time and is carried out repeatedly against their peers. In 2024, 527 cases of bullying occurred in educational environments in Indonesia. In this article, a mathematical model of a bullying case is formulated in non-dimensional form, taking into account the possibility that bullying victims can become bullies. Based on the model analysis, we obtained an equilibrium point. The equilibrium point is locally asymptotically stable according to the Routh-Hurwitz criterion. Next, the numerical simulation of the model is demonstrated to support the analytical results.